(NsTATXI OB ISKUSSTWE I LITERATURE (B/s (N~ASTX (B15s - (NtOLSTOJ(B, (NlEW nIKOLAEWI^s ((NmOSKWA(B:s (NhUDOVESTWENNAQ LITERATURA(B,s, 1983)
(Nw (B15 (NTOM sOBRANIQ SO^INENIJ WO[LI STATXI OB ISKUSSTWE I LITERATURE(B.s
rus
Keywords: (NsTATXI I ZAMETKIs